Splenic marginal zone lymphoma: a literature review of diagnostic and therapeutic challenges - Santos, Tayse Silva dos (Rev Bras Hematol Hemoter, 2017)
Splenic marginal zone lymphoma (SMZL) is a low-grade B-cell non-Hodgkin's lymphoma characterized by massive splenomegaly, moderate lymphocytosis with or without villous lymphocytes, rare involvement of peripheral lymph nodes and indolent clinical course. As a rare disease, with no randomized prospective trials, there is no standard of care for SMZL so far. Splenectomy has been done for many years as an attempt to control disease, but nowadays it has not been encouraged as first line because of new advances in therapy as rituximab, that are as effective with minimal toxicity. Facing these controversies, this review highlights advances in the literature regarding diagnosis, prognostic factors, treatment indications and therapeutic options.